Opium use and mortality in Golestan Cohort Study: prospective cohort study of 50 000 adults in Iran - Khademi, Hooman (BMJ Publishing Group Ltd., 2012)
Objectives To investigate the association between opium use and subsequent risk of death. Design Prospective cohort study. Setting The Golestan Cohort Study in north-eastern Iran collected detailed validated data on opium use and other exposures at baseline. Participants were enrolled between January 2004 and June 2008 and were followed to May 2011, with a follow-up success rate of over 99%. Participants 50 045 participants aged 40-75 at baseline. Main outcomes Mortality, all cause and major subcategories. Results 17% (n=8487) of the participants reported opium use, with a mean duration of 12.7 years. During the follow-up period 2145 deaths were reported. The adjusted hazard ratio for all cause mortality associated with ever use of opium was 1.86 (95% confidence interval 1.68 to 2.06). Opium consumption was significantly associated with increased risks of deaths from several causes including circulatory diseases (hazard ratio 1.81) and cancer (1.61). The strongest associations were seen with deaths from asthma, tuberculosis, and chronic obstructive pulmonary disease (11.0, 6.22, and 5.44, respectively). After exclusion of people who self prescribed opium after the onset of major chronic illnesses, the associations remained strong with a dose-response relation. Conclusion Opium users have an increased risk of death from multiple causes compared with non-users. Increased risks were also seen in people who used low amounts of opium for a long period and those who had no major illness before use.